2020
DOI: 10.1101/2020.04.03.024372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focused ultrasound stimulates ER localized mechanosensitive PANNEXIN-1 to mediate intracellular calcium release in invasive cancer cells

Abstract: Focused ultrasound (FUS) is a rapidly developing stimulus technology with the potential to uncover novel mechanosensory dependent cellular processes. Since it is noninvasive, it holds great promise for future therapeutic applications in patients used either alone or as a complement to boost existing treatments. For example, FUS stimulation causes invasive but not noninvasive cancer cell lines to exhibit marked activation of calcium signaling pathways. Here, we identify the membrane channel PANNEXIN1 (PANX1) as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Indeed, recent evidence suggests that numerous calcium channels localized to the ER (e.g. Pannexin-1 and Piezo) can be activated by extracellular mechanical stimuli such as uniaxial stretching, focused ultrasound and lasertweezer-traction at the plasma membrane [32][33][34] . We consistently found that cells ligated to an ECM in 2D generate high actin tension and simultaneously develop dysregulated calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, recent evidence suggests that numerous calcium channels localized to the ER (e.g. Pannexin-1 and Piezo) can be activated by extracellular mechanical stimuli such as uniaxial stretching, focused ultrasound and lasertweezer-traction at the plasma membrane [32][33][34] . We consistently found that cells ligated to an ECM in 2D generate high actin tension and simultaneously develop dysregulated calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A table of the renormalized values of tension is shown in Table S1. A typical value of a0 for the systems we model is a0=10 nm; this value ensures that our choices of c0=0.4-0.8 a0 -1 and e 2 =6.3a0 2 , are primed to model curvature sensing proteins such with BAR and ENTH domains, as justified in previous works 32,33 . With this choice of the value for the scale parameter a0, the characteristic size of the protrusion we model is of diameter 10a0 (as set by the Ising potential), which amounts to 100 nm; this value is consistent with the diameter of membrane protrusions observed in cell studies [W. Guo, private communication, 2015].…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that the connexin 43 hemichannel works as a mechanosensor in hMSC that releases ATP to the extracellular space in response to low-intensity ultrasound [18]. In addition, we recently showed that ultrasound-induced ATP release was reduced significantly when the pannexin 1 hemichannel was either inhibited or knocked down in the prostate PC-3 cancer cells [57]. Ultrasound is a very unique modality that can transmit mechanical energy into tissues deep in the body without an invasive procedure.…”
Section: Discussionmentioning
confidence: 99%